(untitled) (Revista de Crítica Literaria Latinoamericana, 2010)
This article examines the dispute regarding what would be the most effective literary representation that José María Arguedas established with the authors of the so-called Latin American boom, in the Diaries of The Fox from Up Above and the Fox from Down Below. In an argument that develops ideas similar to those proposed by Walter Benjamin in his essay “The Storyteller,” Arguedas stresses the value of the storyteller Carmen Taripha over the literary achievements of the most significant writer of the boom, Gabriel García Márquez. What is important for the literary representation in Arguedas is the transmission of experience, something that his latest novel achieved in the form of the testimony of his own death.